Analisis Pengaruh NIM, LDR, BOPO, dan CAR terhadap Profitabilitas dengan BI-Rate dan Bank Size sebagai Variabel Moderasi: Studi pada Bank Umum Konvensional Terdaftar di BEI Tahun 2019-2023 - Kevin Sukma Adhinugraha; Mahfudz Mahfudz (Faculty of Economics and Business Diponegoro University, 2025)
Banking plays a vital role as an economic driver, which contributes to development, equity, and improving the welfare of society. Profitability is a crucial aspect in measuring the effectiveness of banks as intermediary institutions, where it is influenced by various internal factors such as financial ratios and bank size, as well as external factors such as monetary policy through the determination of the Central Bank Interest Rate (BI-Rate). Therefore, this study takes the title of Analysis of the Effect of NIM, LDR, BOPO, CAR on Profitability with BI-Rate and Bank Size as Moderating Variables (Study on Conventional Commercial Banks Listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 Period).The research sample is 39 conventional commercial banks listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period (5 years), with a total of 195 observations. Data was obtained from the Bank's Annual Report in that period through Bloomberg Terminal. The analysis was carried out by multiple linear regression with Moderated Regression Analysis (MRA) method.The results show that the model is simultanously significant (F = 0.0000). LDR has a significant positive effect on ROA, while CAR has a significant negative effect on ROA. BI-Rate acts as a pure moderator, where BI-Rate itself is insignificant to ROA but negatively moderates CAR to ROA. Meanwhile, Bank Size acts as a quasi moderator, where it has a significant positive effect on ROA while negatively moderating LDR on ROA and positively moderating CAR on ROA.